Results of Hallux Valgus Surgery in Diabetic Patients with Percutaneous First Metatarsal Osteotomy and K-Wire Fixation - Ding Cheng Yang MD, DPM, PhD (Foot & Ankle Orthopaedics)
Category: Diabetes; Bunion Introduction/Purpose: Diabetes is a rising global prevalent disease. Patients with diabetes mellitus (DM) have potential neurovascular changes in their feet and ankles, which makes them vulnerable to surgical wound infection, as well as delayed healing of bones and wounds. Whether diabetes affects the outcomes of hallux valgus surgery is unknown. This study aims to investigate the impact of diabetes on the outcomes of hallux valgus surgeries using the minimally invasive surgery (MIS) technique. Methods: A total of 319 patients were included in this study, and 342 MIS Hallux Valgus procedures were performed from 2018 to 2023 at our institutions. Patients were divided into diabetic (DM-HV) and non-diabetic (NDM-HV) groups. DM was defined by elevated glycated hemoglobin A1c (HbA1c), blood glucose values, and medication history. MIS hallux valgus correction was performed with minimal surgical incisions of less than 2cm in length. Percutaneous Chevron first metatarsal osteotomies using the Shannon burr and Kirschner wire fixation were guided under fluoroscopy. The DM-HV group included 46 feet of 45 patients, and the NDM-HV group included 296 feet of 274 patients. Clinically, the preoperative and final follow-up American Orthopedic Foot & Ankle Society (AOFAS) score, radiographic hallux valgus angle (HVA), and first intermetatarsal angle (IMA) were evaluated. Procedure durations and patient complications were also assessed. Results: In the DM-HV group, the patients ranged from 51 to 87 years with a mean age of 73 (male 14, female 32). In the NDM-HV group, the patients ranged from 34 to 97 years, with a mean age of 58 (male 49, female 247). The mean AOFAS score improved from 41.42 preoperatively to 93.10 postoperatively in the DM-HV group, and from 42.50 to 94.38 in the NDM-HV group. 4.3% of complications in the DM-HA group and 4.7% in the NDM-HA group were in this study. Surgical complications included: K-wires broke, hallux varus, under correction, transfer metatarsalgia, medial incision dehiscence, and adhesion. There was no difference between DM-HV and NDM-HV groups in improved AOFAS scores, radiological deformity correction, durations of surgery, complications, and reoperation rates. Conclusion: Chevron osteotomy using the Shannon burr with Kirschner (K)-wire fixation is a safe, effective, reliable procedure on both non-diabetic patients and diabetic patients. Hallux Valgus MIS surgery with the K-wire fixation on diabetic patients has no high complication rate. Minimally invasive surgery for hallux valgus correction resulted in improved AOFAS scores and radiological outcomes, fewer complications, and a shorter duration of surgery. MIS can be a better option for correcting hallux valgus deformities in diabetic patients.